PRICE FLUCTUATION OF HORTICULTURAL COMMODITIES IN WEST NUSA TENGGARA PROVINCE IN 2024: ANALYSIS OF VEGETABLE AND FRUIT PRICE STABILITY ON CONSUMER PURCHASING POWER - I PUTU BUDA YASA (Journal of Tabulation Economic Data, 2025)
Horticultural commodities play a crucial role in household food consumption and economic stability in Indonesia. This study examines the price fluctuation patterns of vegetables and fruits in West Nusa Tenggara (NTB) Province throughout 2024, focusing on their impact on consumer purchasing power. Using quantitative descriptive analysis of secondary data from Statistics Indonesia (BPS) NTB Province 2024, this research analyzed monthly price variations of six key commodities: fresh spinach (bayam), green mustard (sawi hijau), carrots, milk bananas, papaya, and imported oranges across three cities (Mataram, Bima, and Sumbawa District). The findings reveal significant seasonal fluctuation patterns, with prices increasing during the dry season (April-June) and declining during peak harvest periods. Green mustard exhibited the highest volatility with a coefficient of variation (CV) of 17.9%, while carrots showed the most stable prices at 8.5% CV. Bima City recorded the highest average prices for most commodities due to elevated distribution costs and supply dependency on Lombok region. The price fluctuations significantly affected consumer purchasing power, particularly among low-income households who tend to reduce consumption or shift to high-carbohydrate alternatives during price spikes. The study recommends strengthening the horticultural logistics system, establishing central horticultural markets, and implementing real-time digital price monitoring systems to maintain market stability and protect consumers. These findings provide valuable insights for policymakers in developing effective price stabilization strategies for horticultural commodities in regional food security planning.